Sistem Pendukung Keputusan Penentuan Tingkat Kecanduan Masyarakat Terhadap Rokok dengan Metode Fuzzy Mamdani - Daniel Andre Marpaung; Murni Marbun (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
A person's addiction to smoking can be seen from the characteristics of the cigarette addict, including: difficulty controlling the desire to smoke, high appetite, frequent coughing, sleep disturbances, and difficulty concentrating. A person's addiction to cigarettes can have a bad impact on the health of that person. The research used the Fuzzy Mamdani method. The system was built using the Hypertext Preprocessor (PHP) programming language. The database management system uses My Structured Query Language (MYSQL). The criteria for the level of community addiction to cigarettes are cost, smoking frequency, and the environment. This study aims to design a Decision Support System for determining the level of community addiction to smoking and applying the Fuzzy Mamdani method for determining the level of community addiction to cigarettes. So it can be concluded that the person's level of addiction is at number 13 or categorized as CANDU.